2022
DOI: 10.1111/josh.13196
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Benefits of Brief Classroom‐Based Physical Activity Interventions on Primary School‐Aged Children's Enjoyment and Subjective Wellbeing: A Systematic Review

Abstract: BACKGROUND: Engaging in classroom-based physical activity (PA) breaks may help increase children's subjective wellbeing and enjoyment of PA, important precursors for children to remain engaged in PA. We conducted a systematic review to investigate the effect of brief classroom-based PA interventions on primary school children's subjective wellbeing and enjoyment of PA. METHODS: Databases were reviewed between the earliest date of records and April 2020. Eligibility criteria included peer-reviewed empirical qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 68 publications
1
10
0
2
Order By: Relevance
“…The results of this scoping review are consistent with the results reported by other systematic reviews focused on the child population, where physical activity is positively associated with psychological health (Biddle et al, 2019;Papadopoulos et al, 2022;Pascoe et al, 2020;Poitras et al, 2016;Rodriguez-Ayllon et al, 2019), and physical activity at school is positively associated with psychological health (Andermo et al, 2020;Vaquero-Solís et al, 2020). However, unlike the systematic reviews mentioned above, in this scoping review there was a paucity of studies evaluating mental health symptoms such as anxiety and depression.…”
Section: Psychological Outcomes Of Classroom-based Physical Activity ...supporting
confidence: 88%
See 1 more Smart Citation
“…The results of this scoping review are consistent with the results reported by other systematic reviews focused on the child population, where physical activity is positively associated with psychological health (Biddle et al, 2019;Papadopoulos et al, 2022;Pascoe et al, 2020;Poitras et al, 2016;Rodriguez-Ayllon et al, 2019), and physical activity at school is positively associated with psychological health (Andermo et al, 2020;Vaquero-Solís et al, 2020). However, unlike the systematic reviews mentioned above, in this scoping review there was a paucity of studies evaluating mental health symptoms such as anxiety and depression.…”
Section: Psychological Outcomes Of Classroom-based Physical Activity ...supporting
confidence: 88%
“…These physical activity interventions have shown increasing evidence of positive effects (McDonald et al, 2018) in the physical activity levels (Masini et al, 2020), academic performance (Bedard et al, 2018;Watson et al, 2017), and cognitive functions (Daly-Smith et al, 2018;Donnelly et al, 2016), and to a lower extent in improving indicators associated with psychological health. In this area, a recent systematic review that included 15 articles in a total sample of 6286 boys and girls from 148 primary schools (Papadopoulos et al, 2022) points out that physical activity in the classroom can affect the enjoyment of physical activity, self-efficacy in learning with video exercises, quality of life and self-confidence (Papadopoulos et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…De igual manera, se evidencia mayor fortalecimiento de la autoimagen corporal, el autoconcepto propio y la persistencia para alcanzar las metas propuestas (Menéndez & González, 2019). Por último, la AF promueve un proceso dinámico de enseñanza-aprendizaje en cooperación con los demás, satisface la necesidad de colaboración, respetando y evidenciando las pautas y el respeto a los derechos de los demás (Papadopoulos, et al, 2022). Por tanto, la promoción de la AF en la infancia es fundamental para alcanzar un estilo de vida saludable.…”
Section: Introductionunclassified
“…Active breaks may be highly relevant for the acquisition of PA benefits. Previous studies have shown that active breaks based on educational and health interventions have led to improvements in participants’ fitness and health [ 21 , 22 ], self-efficacy [ 23 ], quality of life and self-confidence [ 24 ].…”
Section: Introductionmentioning
confidence: 99%